Հայ հոգեւորականի կերպարն օտարների նօթերում - Մադոյեան, Արշակ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В докладе обсуждаются визиты американских и английских мис- сионеров в Армению и армянскую диаспору в разных странах в XIX веке, а также их мнения об армянском духовенстве и Армянской Церкви. Исходя из мнений зарубежных миссионеров исследователей, переведенных с английского и опубликованных в журнале «Эчмиадзин», можно удостовериться, что армянский священнослужитель был приверженцем и защитником национальной Церкви, национальной культуры и образования и, наконец, национальной идентичности. The article discusses the visits of American and English missionaries to Armenia and the Armenian diaspora in different countries in the 19th century, as well as their views on the Armenian clergy and the Armenian Church. Based on the opinions of foreign missionaries and researchers, which were translated from English and published in “Etchmiadzin” magazine, one can make sure that the Armenian clergymen were adherents and defenders of the national Church, national culture, education and, finally, of the national identity.
Keywords: Բանասիրություն; Հայոց եկեղեցիներ